Influence of high-energy milling and heat treatment on the thermal and mechanical properties of a ZrMgMo3O12p/2024Al composite. Issue 10 (July 2019) - Yang, Junrui; Liu, Zhongxia; Yang, Ruibin; Zhi, Qian; Yang, Mengjie; Zhang, Yazhou; Liang, Erjun
Abstract: In this study, ZrMgMo3 O12particle (p) /2024Al composites were fabricated with 10 vol% of a near-zero expansion material, ZrMgMo3 O12, as a reinforcement via high-energy milling followed by vacuum hot pressing (VHP). The influences of the milling conditions and the heat treatment on the hardness, thermal expansion properties and dimensional stabilities of the composites were studied. The results show that high-energy (HE) ball milling refined the ZrMgMo3 O12 particles and the grains of the α-Al matrix, increased the hardness and decreased the coefficients of thermal expansion (CTEs) of the ZrMgMo3 O12p /2024Al composites. Compared with those of the ZrMgMo3 O12p /2024Al composites prepared via low-energy (LE) milling, the hardness value increased to 183 HV from 91.8 HV and the CTE decreased to 16 × 10 −6 /°C (RT - 400 °C) from 22 × 10 −6 /°C (RT - 300 °C). Heat treatment of the solution for 24 h followed by ageing at 190 °C for 5 h (i.e., P2 process) further increased the hardness value to 277 HV and decreased the CTE to 13.4 × 10 −6 /°C (RT - 400 °C), which represent an increase of 83% and decrease of 39%, respectively, compared with those of the heat-treated LE ZrMgMo3 O12p /2024Al composites. High-energy ball milling and heat treatment could improve the dimensional stabilities of the composites as well. In particular, the HE ZrMgMo3 O12p /2024Al composites heat treated with the P2 process showed no variation in their hysteretic strain or CTEs during thermal cycling from RT to 400 °C. Therefore, the P2 HE ZrMgMo3 O12p /2024Al composites are in a thermostable state and have the best dimensional stabilities of the tested samples.